Innovation management, personnel management and time management as integrated tools for enhancing the efficiency of modern enterprises - Krainik, O. (Економічний вісник Донбасу, 2025)
Modern enterprises face rapid changes, globalization, digitalization, and growing competition, requiring quick adaptation, efficient resource management, and continuous development. Innovation management, personnel management, and time management form an integrated toolkit that enhances organizational efficiency. Their combined application creates a synergistic effect, improving productivity, competitiveness, and adaptability. The study highlights the importance of integrating these disciplines through digital platforms, HR technologies, and time management methods to support sustainable development and long-term growth. Сучасні підприємства стикаються зі швидкими змінами, глобалізацією, цифровізацією та зростаючою конкуренцією, що вимагає швидкої адаптації, ефективного управління ресурсами та постійного розвитку. Управління інноваціями, управління персоналом та управління часом утворюють інтегрований інструментарій, який підвищує ефективність організації. Їх спільне застосування створює синергетичний ефект, покращуючи продуктивність, конкурентоспроможність та адаптивність. У дослідженні підкреслюється важливість інтеграції цих дисциплін за допомогою цифрових платформ, HR-технологій та методів управління часом для підтримки сталого розвитку та довгострокового зростання.